2014
DOI: 10.1111/aab.12117
|View full text |Cite
|
Sign up to set email alerts
|

Potential distribution of Avena sterilis L. in Europe under climate change

Abstract: Avena sterilis (sterile oat) is one of the most extended and harmful weeds in Mediterranean cereal crops. A process‐based niche model for this species was developed using CLIMEX. The model was validated and used to assess the potential distribution of A. sterilis in Europe under the current climate and under two climate change scenarios. Both scenarios represent contrasting temporal patterns of economic development and CO2 emissions. The projections under current climate conditions indicated that A. sterilis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 30 publications
0
10
0
1
Order By: Relevance
“…This is a fourth-generation atmospheric general circulation model, ECHAM4, coupled with an ocean general circulation model, OPYC3 (Castellanos-Frías et al, 2014). The target years were set to 2020, 2050 and 2070 using two different standardized scenarios.…”
Section: Climate Scenariosmentioning
confidence: 99%
“…This is a fourth-generation atmospheric general circulation model, ECHAM4, coupled with an ocean general circulation model, OPYC3 (Castellanos-Frías et al, 2014). The target years were set to 2020, 2050 and 2070 using two different standardized scenarios.…”
Section: Climate Scenariosmentioning
confidence: 99%
“…Many species seeds found to response to various amplitudes of temperature fluctuation (Thompson and Grime, 1983). Castellanos-Frias, et al (2014) reported A. sterilis to have a high adaptation in a global geographical distribution with a wide range of temperatures. L. rigidum is also reported to be adapted to a broad range of temperatures for germination between 12 and 30 ⁰ C (Turner, et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Sterile oat (Avena sterilis) is reported as one the most widespread and harmful weed species in Mediterranean climate (Castellanos-Frias, 2014). It is also considered to be common grass weed of cereals in Mediterranean countries (Dimakakos, 1983) and India (Balyan, et al, 1991) and North America (Carlson and Hill, 1985) and in Europe and Australia (Torner, et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Avena sterilis L (Sterile oat) is one the most widespread, common and harmful to arable crop weed species of Mediterranean climates (Damanakis, 1983 andCastellanos-Frias, 2014). It is also widespread across the whole of Europe (Tutin et al, 1980), India (Balyn et al, 1991), North America (Carlson & Hill, 1985) and Australia (Torner et al, 1984).…”
Section: Introductionmentioning
confidence: 99%